Increase Crop Resilience to Heat Stress Using Omic Strategies - Zhou, Rong; Jiang, Fangling; Niu, Lifei; Song, Xiaoming; Yu, Lu; Yang, Yuwen; Wu, Zhen (Frontiers in Plant Science, 2022)
Varieties with high resilience of various crops are urgently needed in order to feed increased population in climate change conditions. Human activities and climate change led to frequent and strong weather fluctuation, which then caused various abiotic stresses to crops. The understanding of crops’ responses to abiotic stresses in different aspects including genes, RNAs, proteins, metabolites and phenotypes can facilitate crop breeding. Using multi-omics methods, mainly genomics, transcriptomics, proteomics, metabolomics and phenomics, to study crops’ response at abiotic stresses will generate a better, deeper and more comprehensive understanding. More importantly, multi-omics can provide multiple-layers information of biological data to understand plant biology, which will open windows for new opportunities to improve crop resilience and tolerance. However, the opportunities and challenges coexisted. Interpretation of the multi-dimensional data from multi-omics and translation of the data into biological meaningful context remained a challenge. More reasonable experimental design starting from sowing seed, cultivating plant, collecting and extracting sample were necessary for multi-omics study as the first step. The normalization, transformation and scaling of single omic data should take the integration of multi-omics into consideration. This review reports current study of crops at abiotic stresses in particular heat stress using omics, which will help to accelerate crop improvement to better tolerate and adapt to climate change.